RUH SAĞLIĞI VE HASTALIKLARI HEMŞİRELİĞİ DERSİNİ YÜZ YÜZE VE UZAKTAN EĞİTİMLE ALAN ÖĞRENCİLERİN DERSİN KAZANIMLARI VE PSİKİYATRİ HEMŞİRELİĞİNİ ALGILAMA AÇISINDAN KARŞILAŞTIRILMASI - ŞİMŞEK ARSLAN, Buket and ÇAKIR, Cansu and ERGÜN, Gül (Göbeklitepe Medical Science Journal, 2022)
The aim of the study is to compare the students taking the Psychiatric Mental Heatlh Nursing (PMHN) course with faceto-face and distance education in terms of the learning outcomes of the course and the perception of psychiatric nursing. The sample of this descriptive study consisted of 229 students of PMHN course in the academic years of 2019-2020 and 2020-2021 and volunteered to participate in the research. Data were collected online with Personal Information Form and Psychiatric Nursing Perception Scale (PNPS). When the participants’ choice of face-to-face or distance education was evaluated, almost all of the participants (96.2%) who received face-to-face education preferred same method. Most of the participants who received distance education (82.1%) stated that they wanted to take course with face-to-face education. There was no statistically significant difference between the participants who received face-to-face education and those who received distance education in terms of PNPS scores. As a result, although it has been determined that there is no difference in terms of the learning outcomes of the course and the perception of psychiatric nursing in distance education students, the students want to receive face-to-face education and work with cases in clinical practice.